Drying Performance and Aflatoxin Content of Paddy Rice Applying an Inflatable Solar Dryer in Burkina Faso - Sebastian Romuli; Steffen Schock; Marius Kounbèsiounè Somda; Joachim Müller (Applied Sciences, 2020)
The drying performance of paddy rice using an inflatable solar dryer (ISD), or also known as GrainPro® Solar Bubble Dryer™, was evaluated and compared to conventional sun drying in Burkina Faso. Drying time was around eight hours. Thermal imaging was conducted to observe temperature distribution in the ISD during drying and mixing. Shadow casting was observed in the ISD due to the round shape of the black plastic film, which reduced the temperature of the paddy rice to about 10 °C. The temperature inside the ISD was up to 13 °C higher than the ambient temperature, whereas the temperature of paddy rice on the top layer was about 5 °C higher than on the bottom. The final moisture content of paddy rice dried in the ISD and under the sun was not considerably different. Under certain circumstances, impurities in paddy rice dried in the ISD could be substantially lower than for sun drying. The aflatoxin level of paddy rice was under the maximum limit of the EU regulation. Drying paddy rice seemed to be effective to remove aflatoxin type AFG2 content. Further adaptation of the ISD design for drying operations on rough surfaces and sandy soils is suggested.